Public Policy Innovations Related to Millennial Farmers in Indonesia - Monalisa, Monalisa; Hasniati, Hasniati; Susanti, Gita; Abdullah, Muh.Tang (Journal of Management and Administration Provision, 2025)
This study aims to analyze the public policy of the Indonesian government in the Millennial Farmer program. This program is expected to attract the interest of the younger generation to be actively involved in the agricultural sector through a digital entrepreneurial approach. The research method uses a literature study that aims to examine various reference sources related to public policy and innovation in the Millennial Farmer program in Indonesia. Rogers' diffusion of innovation theory is used as an analytical framework to measure the extent to which digital technology can be adopted by millennial farmers. Five main dimensions relative advantage, suitability, complexity, trialability, and observability are the assessment indicators. The results of the study show that although this program offers relative advantages in increasing productivity and market access, there are still obstacles in the complexity and trialability aspects due to limited training and minimal technology trial facilities in the field. The primary survey revealed that 65% of millennial farmers have used agricultural applications, but 60% of them have difficulty understanding digital features and 50% have internet infrastructure constraints. Observability is still low due to the lack of real representation of successful farmers as local role models. The conclusion of this study confirms that the effectiveness of public policy in encouraging the adoption of innovation is greatly influenced by user readiness, infrastructure support, and active involvement of local governments. Therefore, a more adaptive, decentralized, and responsive policy strategy to local needs is crucial to accelerate the transformation of the technology-based agricultural sector.